The Influence of Family Conflicts on the Formation of Deviant Behavior in Adolescents (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article provides information about the causes and manifestations of deviant behavior in adolescents. The opinions of scientists on family conflicts and their influence on the formation of deviant behavior in adolescents are presented.